Effect of Ti4+ on the structure of nepheline (NaAlSiO4) glass. (1st December 2020) - Nienhuis, Emily T.; Marcial, José; Robine, Thibaut; Le Losq, Charles; Neuville, Daniel R.; Stennett, Martin C.; Hyatt, Neil C.; McCloy, John S.
Abstract: In this study, the effect of Ti 4+ on the structure of nepheline glass (NaAlSiO4 ) is investigated as SiO2 is systematically replaced with TiO2 . Traditionally, TiO2 is considered to be a nucleating agent for silicate crystallization but can also be incorporated into the glass network in relatively large amounts as either a network former or modifier depending on its coordination with oxygen. To determine the effect of Ti 4+ on the structure of nepheline glass, X-ray and neutron pair distribution function (PDF) analysis paired with Empirical Potential Structure Refinement (EPSR) were conducted and are supplemented with Raman spectroscopy, electron probe microanalysis, and X-ray absorption spectroscopy (including Extended X-ray Absorption Fine Structure, EXAFS). Through these methods, it has been found that up to 15 mol% (16 wt%) TiO2 can incorporate into the glass network as a four-fold coordinated species, with a minor contribution of higher coordinated Ti. Between NaAlTi0.1 Si0.9 O4 and NaAlTi0.2 Si0.8 O4, EXAFS suggests a local structure change in the second coordination sphere of Ti, which changes from Ti-Ti to Ti-Al. Raman spectroscopy also suggests that as Ti content increases, the Na environment becomes more ordered. These results suggest that the Ti activity coefficient and its isotopic fractionation for magnetite and other Ti-bearing minerals should be fairly constant in polymerized melts, such as metaluminous and peraluminous rhyolites.